(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
A total of 320 bacteria isolated from marketable size and diseased mud crab (Scylla serrata) at a commercial farm. The isolated bacteria were Aeromonas spp. n = 70, Edwardsiella tarda n = 50, Vibrio alginolyticus n = 40, Vibrio parahaemolyticus n = 20, Salmonella spp. n = 70 and Klebsiella spp. n = 70. All the bacterial isolates were tested for antibiotic susceptibility against 16 types of antibiotics by using disk diffusion method. The antibiotics tested in this study were nalidixic acid (30 ug/disk), oxolinic acid (2 ug/disk), compound sulphonamides (300 ug/disk), doxycycline (30 ug/disk), tetracycline (30 ug/disk), novobiocin (30 ug/disk), chloramphenicol (30 ug/disk), kanamycin (30 ug/disk), sulphamethoxazole (25 ug/disk), flumequine (30 ug/disk), erythromycin (15 ug/disk), ampicillin (10 ug/disk), spiramycin (100ug/disk), oxytetracycline (30 ug/disk), amoxycillin (25 ug/disk) and fosfomycin (50 ug/disk). Heavy metal resistance pattern of the present bacterial isolates was also characterized against mercury (Hg2+), chromium (Cr6+), copper (Cu2+), and Zinc (Zn2+) by using two fold agar dilution method. The percentage of antibiotic sensitivity of the present bacterial isolates was ranged from 12.5% to 100% in which most of the present bacteria isolates were not sensitive to ampicillin whereas all the bacteria isolates were sensitive to nalidixic acid, flumequine and oxytetracycline. Overall, the total of antibiotic sensitive case was reported as 72.7% whereas antibiotic resistance and intermediate sensitive case was recorded as 19.7% and 7.4%, respectively. The Multiple Antibiotic Resistance (MAR) values were range of 0.03 to 0.29 in which Aeromonas spp (0.29) showed the highest value of MAR. This was followed by Salmonella spp. (0.21) and Klebsiella spp. (0.21), Edwardsiella tarda (0.20), Vibrio alginolyticus (0.09) and Vibrio parahaemolyticus (0.03). The MAR value indicated that the commercial S. serrata were not contaminated to the test antibiotics. Furthermore, low resistance activity of the present bacterial isolates to the tested heavy metals (Cr6+: 20.7 % to 30.8 %, Zn2+: 0 % to 40 %, Cu2+: 18.8 % to 25 % and Hg2+: 30 % to 33.3 %) was observed.